2021
DOI: 10.1016/j.drugalcdep.2020.108368
|View full text |Cite
|
Sign up to set email alerts
|

Pain catastrophizing predicts alcohol craving in heavy drinkers independent of pain intensity

Abstract: Background: Chronic pain and alcohol use disorder (AUD) are often co-occurring conditions. Pain catastrophizing, an emotional component of pain, and pain intensity are related to alcohol use as a coping mechanism; however, how pain interacts with tonic alcohol craving is an understudied area. This study sought to determine the unique and independent effects of pain intensity and pain catastrophizing on alcohol craving in heavy drinkers.Method: Non-treatment seeking heavy drinkers (n = 128) completed self-repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 65 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…That study, which tested associations between pain and alcohol consumption and motives among 128 patients seeking AUD treatment, also examined pain catastrophizing as a predictor variable of all outcomes. 91 Results indicated that pain catastrophizing was associated with greater alcohol craving, AUD symptoms, and normalizing drinking motives, regardless of pain intensity.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…That study, which tested associations between pain and alcohol consumption and motives among 128 patients seeking AUD treatment, also examined pain catastrophizing as a predictor variable of all outcomes. 91 Results indicated that pain catastrophizing was associated with greater alcohol craving, AUD symptoms, and normalizing drinking motives, regardless of pain intensity.…”
Section: Resultsmentioning
confidence: 89%
“…Among a sample of patients seeking treatment for AUD ( N = 128), high-intensity pain ratings (vs. no or low-intensity pain) were associated with a greater number of self-reported drinks per day and higher alcohol craving, and participants with high-intensity pain were more likely to report normalizing motives for drinking (i.e., “to feel normal”). 91 Finally, researchers recently developed and validated the Expectancies for Alcohol Analgesia measure, which assesses perceived likelihood of pain relief from drinking. In a sample of 273 people who reported chronic pain and current alcohol use, expectancies for analgesia were associated with reporting greater frequency and quantity of alcohol use and identifying coping as a motive for drinking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, psychosocial factors are also highly present in patients with alcohol abuse and can be attributed to abnormalities in the reward system of the brain [ 114 ]. Additionally, a recently published study demonstrated that chronic pain patients with high levels of pain catastrophising are more likely to be heavy drinkers [ 115 ]. General advice on alcohol consumption after cancer is currently not possible due to the high variability of results in different CSs.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Hyper-negative emotional states and hyperalgesia are both consequences of repeated alcohol use [ 46 ] and may contribute to an increase in alcohol use as a compensatory mechanism [ 47 ]. Among heavy drinkers, the negative emotional components of pain (i.e., pain catastrophizing) can enhance alcohol craving more than physical pain [ 48 ].…”
Section: Introductionmentioning
confidence: 99%